Analysis of User Needs for Collection Development Activity in Mahkamah Agung Republik Indonesia Library - Grataridarga, Niko (Record and Library Journal, 2018)
This study discusses the activities of analyzing user needs in developing collections in specialized libraries. This study aims to identify the practices and constraints faced by librarians in conducting user needs analysis activities at the Mahkamah Agung Library. The activity of analyzing user needs becomes important as an initial step and benchmark in developing collections. This research is a qualitative research using a case study method. The results of this study show that the Mahkamah Agung Library has not analyzed the needs of users in depth. This causes librarians to be confused about how to develop collections cannot determine the procurement of collections. Then more in-depth analysis is needed by auditing information and interviews with users.